Complications associated with cardiac resynchronization therapy upgrades versus de novo implantations. (3rd August 2018) - Sidhu, Baldeep S.; Gould, Justin; Sieniewicz, Benjamin J.; Porter, Bradley; Rinaldi, Christopher A.
ABSTRACT: Introduction : A significant number of patients undergo upgrade to cardiac resynchronization therapy (CRT). These patients tend to differ from individuals undergoing de novo CRT implantations both in terms of their baseline demographics and the etiology underlying their heart failure. Areas covered : There are several factors that need to be considered when upgrading patients to CRT, such as, venous patency. Potentially, these conditions can cause issues which may result in procedures being more difficult than de novo implantations. This article discusses these issues and compares the rates of procedural-related complications for CRT upgrades and de novo implantations. It discusses the proportion of patients that are likely to respond to CRT with each intervention. Expert commentary : Understanding the relative risks of CRT upgrades versus de novo implantations is important to help operators select the correct initial device and counsel patients accordingly. Growing experience with image-guided implantations and endocardial pacing may prove to be particularly relevant to patients undergoing CRT upgrades.